2022
DOI: 10.1002/cssc.202102533
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Mediated Direct CO2 Capture by a Stackable Bipolar Cell

Abstract: The unprecedented increase in atmospheric CO 2 concentration calls for effective carbon capture technologies. With distributed sources contributing to about half of the overall emission, CO 2 capture from the atmosphere [direct air capture, (DAC)] is more relevant than ever. Herein, an electrochemically mediated DAC system is reported which utilizes affinity of redox-active quinone moieties towards CO 2 molecules, and unlike incumbent chemisorption technologies which require temperature or pH swing, relies sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“… 28 The same group also developed several prototype cells for direct air capture of CO 2 based on AQ polymers. 29 31 It has been reported that oxygen (O 2 ) binding and electrochemical O 2 reduction by these AQ-polymers are crucial side-reactions to be considered. 29 , 32 Very recently, Bui et al investigated the impact of multiple substitutions involving several AQ derivatives with CV and related their findings regarding electrochemical potentials with results obtained via density functional theory (DFT) calculations.…”
Section: Introductionmentioning
confidence: 99%
“… 28 The same group also developed several prototype cells for direct air capture of CO 2 based on AQ polymers. 29 31 It has been reported that oxygen (O 2 ) binding and electrochemical O 2 reduction by these AQ-polymers are crucial side-reactions to be considered. 29 , 32 Very recently, Bui et al investigated the impact of multiple substitutions involving several AQ derivatives with CV and related their findings regarding electrochemical potentials with results obtained via density functional theory (DFT) calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Other electrogenerated nucleophiles based on bipyridine and disulfide chemistries have also been explored ( Ishida et al., 1994 ; Ranjan et al., 2015 ; Singh et al., 2017 ). Whereas reports on proof-of-concept EMCC with redox-active organic carriers are primarily batch processes ( Hemmatifar et al., 2022 ; Liu et al., 2020a , 2020b ; Scovazzo et al., 2003 ; Voskian and Hatton, 2019 ) or supported liquid membranes ( Gurkan et al., 2015 ), the first flow-based prototype was demonstrated recently ( Diederichsen et al., 2022 ). In that study, a naphthoquinone derivative was synthesized, which is a liquid at room temperature (“liquid quinone”).…”
Section: Emcc Mechanisms Compatible With Continuous Flow Processesmentioning
confidence: 99%
“…For example, the recent work by the Hatton group demonstrates a technology that could use much less energy. 64,65 However, there is not enough published data and the technology readiness level is too low to perform an accurate cost assessment, and hence this technology improvement is not considered for analysis in this work.…”
Section: Learning Curves and Modularitymentioning
confidence: 99%